The role of social identity complexity and outgroup aggression - Hoon, En Qi (Nanyang Technological University, 2020)
This paper explores the role of social identity complexity (SIC) on the alleviation of outgroup aggression. Low SIC (LSIC) inolves multiple identities as a single convergent social identity, while high SIC (HSIC) accepts differentiation among ingroup memberships. Studies have shown that HSIC was associated with positive intergroup outcomes like outgroup tolerance and acceptance. Often measured as an outcome, there were few studies that directly manipulated SIC to predict and improve intergroup relations in a competitive setting. The degree of outgroup threat was also manipulated as past research posited that intergroup competition was largely motivated by ingroup love, to protect its members against outgroup threat, than outgroup hate. This study predicted that HSIC favoured helping the ingroup, while LSIC favoured harming the outgroup. A total of 124 undergraduates were recruited. After drawing a social identity map intended to manipulate SIC, participants competed in a revised version of the Intergroup Prison’s Dilemma-Maximizing Difference game, where the participants were given points to keep for themselves or contribute to pools that help the ingroup (Pool A), hurt the outgroup and simultaneously help the ingroup (Pool B), or unique to this study, to exclusively hurt the outgroup (Pool C). Results based on mixed model analyses suggested that most participants favoured Pool A, although LSIC contributed significantly more points to Pool C than HSIC under outgroup threat. Thus, priming HSIC would warrant greater tolerance of outgroup threat and reduced retaliation even out of defence, thereby minimizing outgroup aggression.